iOS hacker's handbook - Miller, Charles 1951- (Wiley, 2012)
"The world loves iOS. Users love the convenience. Black hats love the vulnerability. This book arms you with the knowledge and tools to protect your organization's iOS devices. If you're a developer, it will also help you create hack-resistant applications."--P. [4] of cover-- Source other than Library of Congress.